The Effect of Osseodensification on Implant Stability and Marginal Bone Levels: A Randomized Control Clinical Trial - Ioanna Politi; Bahman Honari; Lewis Winning; Ioannis Polyzois (Clinical and Experimental Dental Research)
ABSTRACT Objectives To compare the implant stability quotient values (ISQ) of implants placed using implant‐specific drills (CD) and osseodensification drills (OD) at three different time points and to determine the effect of both drilling techniques on marginal bone levels. Material and Methods 38 subjects were recruited and ISQ values and radiographic marginal bone levels were recorded after surgery (T1), and also at 3 (T2) and 4–5 months (T3). Clinical and radiographic marginal bone levels were also recorded. Results At T1, mean ISQ values ranged from 65.5 to 81 for the CD group and 29 to 80 for the OD group. For the CD group, ISQ values were 72.20 ± 2.6 (95% CI) at T1, 75.0 ± 2.0 at T2, and 74.8 ± 2.3 at T3. The corresponding ISQ values for the OD group were 68.1 ± 5.6, 71.9 ± 1.6, and 72.2 ± 2.4, respectively. Implants placed using CD drills showed greater stability at 3 months but not at placement or at 4–5 months. No statistically significant differences were identified regarding marginal bone levels between the two groups. Conclusions There was a notable increase in implant stability over time for both treatment modalities. At T2, implants inserted into osteotomies made with standard drills exhibited significantly greater stability compared to those placed using OD drills. However, the clinical relevance of this difference is questionable, as it was not observed at T3. Marginal bone levels were comparable for both groups over all time points. Trial Registration ClinicalTrials.gov identifier: NCT05376020